KERAGAAN DAN BUDIDAYA KOMODITAS PANILI DI INDONESIA (Studi Kasus Kabupaten Minahasa) - ROOSGANDHA ELIZABETH (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Indonesia might be considered estate crops country. Vanilla is one of estate cropscommodity that has significant share of Indonesian foreign exchange revenue. This spicycommodity is one of Indonesian important traditional export commodities in internationalmarkets. As one of prospective export commodity Indonesia should give more attention tothe development this commodity. The data shows recently, however, the trend of decliningthe export demand in the international market, both in volume and value. If it is comparedto other Asian countries, moreover, the decline is shown very significant. In Minahasadistrict in particular, the decline is caused by, among others, traditional crop managementsystem and technology, need high capital if it is cultivate intensively and integrated, andlack of labour knowledge on how to do the best practice in cultivating vanilla. Moreimportantly, price uncertainty and market uncertainty, where up to present price isdetermined mostly by traders, give disincentive and discourage vanilla farmers to improvetheir cultivation practice.